Quantification of health risk due to poor sanitation infrastructure in slums of urban Khulna, Bangladesh. - Islam, S. M. Tafsirul; Kabir, Md. Ahsanul (International Journal of Environmental Health Research, 2025)
Slums worldwide, from Africa to Asia, face inadequate infrastructure, fostering health crises, and hindering progress toward sustainable development goals related to clean water and sanitation. Densely populated slums pose significant health risks due to poor waste management. This study examines the link between sanitation and health risks in 10 slums in Khulna, Bangladesh. The research evaluates 339 randomly selected households using a rapid assessment tool and a detailed survey, with ArcGIS aiding the sampling process. Findings reveal disparities in sanitation infrastructure, with private and public slums facing higher health risks than semi-public ones. About 70% of the slums have a composite risk score above 50%, and 40% are exposed to sanitation crises. Overall, the slums present medium-scale risks due to poor infrastructure, health hazards, and vulnerability. Addressing these challenges requires tackling hazards, exposure, and vulnerability, enhancing access to safe water and sanitation, reducing waterborne diseases, and fostering resilient urban infrastructure. Policymakers should invest in sanitation infrastructure, promote public health education, and implement action plans to improve living conditions in Khulna's slums.